^ - степень
1) (7y^7 - 9b^2)^2 = 49y^14 - 126y^7*b^2 + 81b^4
2) (5x^5 + 11xy^3) = 25x^10 + 110x^6*y^3 + 121x^2*y^6
62х-256=114-38х 351-92х=51-72х
62х+38х=114+256 351-51=92х-72х
100х=370 300=20х
х=370:100 х=300:20
х=3,7 х=15
229-43х=62х-44 405+95х=-55+49х
-43х-62х=-44-229 95х-49х=-55-405
-105х=-273 46х=-460
х=-273:-105 х=-460:46
х= 2,6 х=-10
17*(5+х)-20х=8х-14 29+14(9-у)=19-2у
85+17х-20х-8х=14 29+126 -14у+2у=19
-11х=14-86 -12у=19-29-126
-11х=-72 -12у=-136
х=-72:-11 у=-136:-12
х=6,(54) у=-11,(3)
24х-12*(7+х)=16-8х -15*(4у-3)+37у=42у-111
24х-84-12х=16-8х -60у+45+37у=42у-111
20х=16+84 -65у=-111-45
20х=100 -65у=-156
х=100:20 у=-156:-65
х=5 у=2 33/65
Ответ:
1 - √29; 1 + √29
Пошаговое объяснение:
Пусть x - одно число, а y - второе число. Получим систему уравнений